Lanthanum molybdenum oxide as a new platform for highly selective adsorption and fast separation of organic dyes. Issue 93 (20th September 2016) - Sun, Meng; Ma, Yuan-Yuan; Tan, Huaqiao; Yan, Jian; Zang, Hong-Ying; Shi, Hong-Fei; Wang, Yong-Hui; Li, Yang-Guang
Abstract : A lanthanum molybdenum oxide (La2 Mo2 O9 ) exhibits fast adsorption properties and high selectivity for multi-sulfonic dyes. Abstract : Exploration of new adsorbents for quick and highly selective adsorption and efficient separation of dyes in waste water is in urgent demand due to environmental problems. Herein, a new lanthanum molybdenum oxide adsorbent, La2 Mo2 O9, is prepared by the calcination of a new crystalline compound [La(CH3 COO)(H2 O)]MoO4 (La–Mo ). After the precursor (La–Mo ) is calcined at 600 °C, the as-prepared La2 Mo2 O9 (abbr.La–Mo600 ) exhibits fast and highly selective adsorption for multi-sulfonic dyes. Furthermore, the dyes adsorbed onLa–Mo600 can be easily eluted by a dilute alkaline solution. Thus, it can be used as a new type of adsorbent to separate dye mixtures. TheLa–Mo600 adsorbent possesses excellent stability in the pH range of 1–13 and can be easily re-used seven times with a negligible adsorption decline. This study suggests that the adsorbent, La2 Mo2 O9, may represent a promising new generation of dye adsorbents that can realize quick adsorption, high selectivity and efficient separation of organic dye mixtures.